Stability evaluation of 7% chloral hydrate syrup contained in mono and multi-dose bottles under room and refrigeration conditions - Bustos Fierro, Carolina (2013)
Purpose: To evaluate the stability of an extemporaneously prepared 7% chloral hydrate syrup under different conditions of storage and dispensing. Methods: Three batches of 7% chloral hydrate syrup were prepared. Each batch was stored in 50 light-resistant glass containers of 60 mL with child-resistant caps and in two bottles of 1000 mL to simulate two forms of dispensing, mono and multi-dose, respectively. Twenty five mono-dose bottles and a multi-dose bottle of each batch were stored under room conditions (20 ± 1°C) and the rest of the samples were stored in the fridge (5 ± 2°C). The physical, chemical and microbiological stability was evaluated for 180 days. Stability was defined as retention of at least 95% of the initial concentration of chloral hydrate, the absence of both visible particulate matter, or color and/or odor changes and the compliance with microbiological attributes of non-sterile pharmaceutical products. Results: At least 98% of the initial chloral hydrate concentration remained throughout the 180-day study period. There were no detectable changes in color, odor, specific gravity and pH and no visible microbial growth. These results were not affected by storage, room or refrigeration conditions or by the frequent opening or closing of the multi-dose containers. Conclusions: Extemporaneously compounded 7% chloral hydrate syrup was stable for at least 180 days when stored in mono or multi-dose light-resistant glass containers at room temperature and under refrigeration.